Prepectoral breast reconstruction is safe in the setting of post-mastectomy radiation therapy. Issue 9 (September 2022) - Long, Chao; Kraenzlin, Franca; Aravind, Pathik; Kokosis, George; Yesantharao, Pooja; Sacks, Justin M.; Rosson, Gedge D.
Summary: Background: Many breast reconstruction patients undergo post-mastectomy radiation therapy (PMRT), which is well known to increase the risk of complications. There is limited data on outcomes and safety of prepectoral breast reconstruction in this setting. The purpose of this study was to compare the outcomes of prepectoral versus subpectoral two-stage breast reconstruction in patients undergoing PMRT. Methods: We conducted a retrospective cohort study of two-stage breast reconstructions performed at our institution during a 22-month period. Patients who received PMRT were identified, and two cohorts were created: those who underwent prepectoral versus subpectoral reconstruction. We collected data including patient characteristics, operative variables, and clinical outcomes. Bivariate analyses and multivariable logistic regressions were conducted. Results: We captured 313 patients (492 breasts) that had undergone two-stage reconstruction. A total of 69 breasts received PMRT; 28 were reconstructed prepectorally, and 41 breasts subpectorally. The two cohorts were well matched. We detected no differences in clinical outcomes between the two groups after a median follow-up time of 24 months. There, however, were differences in perioperative variables. Prepectoral reconstruction was associated with a shorter operative time, shorter length of hospital stay, higher cost, and shorter time to final reconstruction. Multivariable logistic regression demonstrated that prepectoral reconstruction is not an independent predictor of adverse events. Conclusions: Although radiation is a known risk factor for many complications following breast reconstruction, prepectoral device placement is safe in this high-risk population. Although the rate of capsular contracture is reported to be higher in the general prepectoral population, this was not found in our radiated prepectoral population.